Spatial and Seasonal Controls on Eddy Subduction in the Southern Ocean - Michael L. Chen; Oscar Schofield (Geophysical Research Letters)
Abstract Carbon export driven by submesoscale, eddy‐associated vertical velocities (“eddy subduction”), and particularly its seasonality, remains understudied, leaving a gap in our understanding of ocean carbon sequestration. Here, we assess mechanisms controlling eddy subduction's spatial and seasonal patterns using 15 years of observations from BGC‐Argo floats in the Southern Ocean. We identify signatures of eddy subduction as subsurface anomalies in temperature‐salinity and oxygen. The anomalies are spatially concentrated near weakly stratified areas and regions with strong lateral buoyancy gradients diagnosed from satellite altimetry, particularly in the Antarctic Circumpolar Current's standing meanders. We use bio‐optical ratios, specifically the chlorophyll a to particulate backscatter ratio (Chl/bbp) to find that eddy subduction is most active in the spring and early summer, with freshly exported material associated with seasonally weak vertical stratification and increasing surface biomass. Climate change is increasing ocean stratification globally, which may weaken eddy subduction's carbon export potential.